2021
DOI: 10.1039/d0ce01705a
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic bending and twisting behaviour of a twin crystal composed of a diarylethene

Abstract: The unusual photomechanical behaviour of a “twin crystal” consisting of a diarylethene derivative was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…77,78 In addition to conventional bending behaviors, rare photomechanical behaviors such as cracking, twisting, and peeling were discovered. [79][80][81][82] Feringa et al synthesized diarylethene (1oRR, Fig. 3a) and grew rod-shaped and thinplate crystals by recrystallization and sublimation.…”
Section: Photocyclizationmentioning
confidence: 99%
“…77,78 In addition to conventional bending behaviors, rare photomechanical behaviors such as cracking, twisting, and peeling were discovered. [79][80][81][82] Feringa et al synthesized diarylethene (1oRR, Fig. 3a) and grew rod-shaped and thinplate crystals by recrystallization and sublimation.…”
Section: Photocyclizationmentioning
confidence: 99%
“…The control of shape and size of diarylethene rodlike crystals can realize the desired photomechanical behaviors. [24][25][26] Bardeen et al used one of the typical approach for synthesis of nanomaterials, the topdown method using the nanoporous inorganic template, to succeed in preparing nanowire crystals of 1,2-bis(2,4-dimethyl-5phenyl-3-thienyl)perfluorocyclopentene, which show the dynamic photoinduced bending behavior. [27] Uchida et al reported that the hollow crystals of 1,2-bis(2-phenyl-5-methyl-3thiazolyl)perfluorocycloheptene prepared by the sublimation method generated the photosalient phenomena mimicking Impatients.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse kinds of photomechanical behaviors such as shape distortion, [15] bending, [16–18] twisting, [19,20] explosion, [21,22] and peeling [23] are induced under the irradiation with UV light in the crystalline phase. The control of shape and size of diarylethene rodlike crystals can realize the desired photomechanical behaviors [24–26] . Bardeen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive crystalline materials that effectively convert external energy into mechanical energy 1,2 have garnered considerable attention in recent years due to their potential advantages in various fields, such as photoswitching, 3 artificial muscles, 4 mechanical arms, 5 and soft robots. 6 It is impressive that stimuli-responsive materials are capable of translating molecular structure perturbation at the molecular level into macroscopic mechanical changes, such as bending, 7 twisting, 8 peeling, 9 fragmenting, 10 swelling, 11 rolling 12 induced by pressure, heat, light and so on. As a simple available stimulation method, light has the advantages of non-contact manner, adjustable wavelength and power, and being less environmentally affected in practical applications.…”
mentioning
confidence: 99%